Whose Talk is Worth More? A Case Study into Questioning Techniques of Native and Non-Native English-Speaking Teachers - Hadjeris, Fadhila; Merrouche, Sarah (Journal of Human Sciences, 2019)
Although the native/non-native speaking teacher dichotomy has stirred up ample scholarly consideration and debate in the field of English language teaching, insufficient attention has been devoted to the interactional features that characterize teacher talk, primarily teachers’ questioning behavior. This study sought to determine the extent to which native and non-native English-speaking teachers diverge in terms of the different types of questions they employ in their classes. Accordingly, eight classes of a native and a non-native speaking teacher at the department of English of Constantine Teachers’ College, Algeria, were audio recorded, transcribed and analyzed according to the different types of questions. The analysis of the results reveals that the native-speaking teacher is more inclined toward promoting a genuine classroom interaction by employing more procedural and referential questions along with an extensive use of comprehension checks, whereas the non-native speaking teacher tended to foster students’ participation through an extensive use of display and convergent questions combined with an abundance of clarification requests and confirmation checks.